Annual Report on Exchange Arrangements and Exchange Restrictions 2002. (Annual Report on Exchange Arrangements and Exchange Restrictions; 2002, 2002)
This 2002 Annual Report on Exchange Arrangements and Exchange Restrictions provides a detailed description of the exchange arrangements and exchange/trade restrictions of individual IMF member countries and Hong Kong Special Administrative Region, as well as Aruba and the Netherlands Antilles. The report highlights that the exchange rate of the Australian dollar is market determined. Licensed foreign exchange dealers may deal among themselves, with their customers, and with overseas counterparties at mutually negotiated rates for both spot and forward transactions in any currency with regard to trade- and nontrade-related transactions.